Aperioptus pictorius Richardson 1848 is a senior synonym of Acanthopsoides molobrion Siebert 1991, and Aperioptus is a senior synonym of Acanthopsoides Fowler 1934 (Cypriniformes: Cobitidae) - Page, Lawrence M.; Tangjitjaroen, Weerapongse (Zootaxa, 2015)
Aperioptus pictorius was described by Richardson in 1848 with limited textual information but with an illustration sufficient to confirm the species as one currently recognized as Acanthopsoides molobrion making Aperioptus a senior synonym of Acanthopsoides Fowler 1934 and A. pictorius a senior synonym of Acanthopsoides molobrion Siebert 1991. Species to be recognized in Aperioptus in addition to A. molobrion are A. gracilis (Fowler 1934), A. gracilentus (Smith 1945), A. delphax (Siebert 1991), A. hapalias (Siebert 1991), and A. robertsi (Siebert 1991). Aperioptus also is a senior synonym of Neacanthopsis Smith 1945, type species Neacanthopsis gracilentus.